The Plasma Soluble Urokinase Plasminogen Activator Receptor Is Related to Disease Activity of Patients with ANCA-Associated Vasculitis - Fei Huang; Yueqiang Li; Ranran Xu; Anying Cheng; Yongman Lv; Qingquan Liu (Hindawi Limited, 2020)
Objective. The soluble urokinase plasminogen activator receptor (suPAR) is associated with kidney diseases and is used as a prognostic factor of renal function progression. The aim of this study was to explore whether circulating suPAR was associated with antineutrophil cytoplasmic autoantibody- (ANCA-) associated vasculitis (AAV) disease activity. Methods. We evaluated 90 AAV patients with follow-up data and 35 normal controls; their plasma suPAR and C-reactive protein (CRP) levels were measured by ELISA. Associations between these levels, clinical parameters, and prognosis were analyzed. Results. Plasma suPAR levels in AAV patients were significantly higher than in healthy controls (5,920.08±3,447.17 vs. 1,441.97±835.04 pg/mL, P<0.001). Furthermore, suPAR was significantly elevated in AAV patients in active stage compared to those in partial remissions (6,492.19±3,689.48 vs. 5,031.86±2,489.01 pg/mL, P=0.039). Correlation analyses demonstrated that suPAR levels positively correlated with initial serum creatinine, BVAS, CRP, and procalcitonin concentration, and negatively correlated with eGFR and C3 circulating levels. In a Kaplan-Meier survival analysis, patients with plasma suPAR levels >5683.3 pg/mL showed poorer survival than patients with lower levels (log-rank, P=0.001). Besides, multivariate analyses confirmed that plasma suPAR levels were an independent adverse prognostic factor for a composite outcome of end-stage renal disease (ESRD) or death, after adjusting for age and gender (HR 1.05, 95% CI=1.01−1.11, P=0.043). Receiver operating characteristic curves showed a suPAR cutoff value >6662.2 pg/mL for composite outcome with 68% sensitivity and 88% specificity, with an AUC=0.82, (95% CI=0.68−0.96, P<0.001). Conclusion. Circulating suPAR levels might be a marker of activity correlated with disease activity in AAV patients, and, to some extent, could be a factor of poor prognosis.